A survey on recycling attitudes of engineering students at Universiti Teknologi Mara Shah Alam - Mohamad, Nur Natasha (2016)
This paper study on the recycling practices of engineering students at UiTM Shah Alam. Previously, there has not been a comprehensive study conducted at UiTM regarding the effectiveness of recycling.. Hence, a proper solid waste management should be enhanced through education among youngsters to ensure an integrated solid waste management. The purpose of the study research is to determine the awareness of engineering students at UiTM on recycling practices through survey and study on the effectiveness of recycling bins at the engineering students’ centre. Questionnaires are being distributed among students where the responses are received directly. The data collected are analyzed using statistical analysis. Results shows that there is significant relationship (p<0.05) between gender and knowledge on recycling using Chi square test and gives an insignificant relationship (p>0.05) between knowledge and awareness of students towards recycling using partial correlation. The results obtained shows that the students’ awareness and knowledge on recycling are unfavorable in the beginning. Most of the students believe that the obstacles that prevent them to recycle are due to the absence of recycling bins or bins are full. As the recycling facilities (recycling bins) are provided, majority of students are aware on the existence of the new recycling bins. Majority of the students do not practice recycling due to the unavailability of the recycling bins at initial phase. However, most of the respondents argued that the bins are usually full, unsure if the products are recyclable, or simply do not bother to care about recycling and believe that recycling is too time consuming. Besides, the results show that the students suggested to provide more recycling bins, making the recycling bins accessible, welcome more education on recycling, request to make the bins more visible using signs and issue fine to those who neglect recycling. A large proportion of students indicated that the instructions given on the recycling bins are clear and understandable. However, throughout the survey period, it can be observed that there are students who are still unaware of what items are recyclable. In addition, question also asked regarding opinion of respondents on contribution to the conservation of environment. Majority of respondents claimed that they will start practicing waste segregation in everyday life. Also, there are respondents who willingly to initiate income generation and creation of future eco entrepreneurs through solid waste management.